Beyond Pre/Post Measurement: Discourse Analysis as an Alternative Methodology in Reporting on an Intervention Programme - Teguh Wijaya Mulya (ANIMA Indonesian Psychological Journal, 2018)
Pre/post comparison has become the most prominent method in reporting on a psychological intervention programme, to the extent that it is almost impossible to report on such programmes without a pre/post evaluation framework. This article introduces discourse analysis methodology as an alternative in reporting on an intervention programme, highlights some of its benefits, and provides an empirical example of its application. Discourse analysis methodology is applied to analyze a diversity workshop, conducted by the author, in a youth refuge in Surabaya (N = 15). Three key discourses were identified, namely, a discourse of (different) abilities, a discourse of peaceful resolution, and a discourse of crime as a natural consequence of inequality; which are discussed in relation to the methodological benefits of the application of discourse analysis, in an intervention programme.